2011
DOI: 10.1007/s00128-011-0485-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Soil Metal Analyses in Sudbury (Ontario, Canada) and Lubumbashi (Katanga, DR-Congo)

Abstract: DR-Congo is a main world producer of copper (Cu) and cobalt (Co). Several hydrometallurgical plants and smelters also produced zinc, arsenic, and cadmium as by-products. In Sudbury (Canada), the production of nickel, copper and other metals has been maintained at high levels while industrial SO(2) emissions have been reduced by approximately 90% through combination of industrial technological developments and legislated controls. Metal analysis in the present study revealed that the levels of copper and cobalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Logging and ore smelting led to a large scale of SO 2 (sulphur dioxide) emissions and metal contamination (copper, Cu; iron, Fe; nickel, Ni and zinc, Zn) [15]. These have resulted in damaged ecosystems with reduced plant growth and population diversities within the region [2,3,5]. Remediation projects were initiated to restore the affected lands and to decrease industrial emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Logging and ore smelting led to a large scale of SO 2 (sulphur dioxide) emissions and metal contamination (copper, Cu; iron, Fe; nickel, Ni and zinc, Zn) [15]. These have resulted in damaged ecosystems with reduced plant growth and population diversities within the region [2,3,5]. Remediation projects were initiated to restore the affected lands and to decrease industrial emissions.…”
Section: Introductionmentioning
confidence: 99%
“…This liming was followed by land fertilization, grass and legume seeding [1,2]. In addition, since 1979, 12 million trees have been planted to complete the reclamation process [2,3,5]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, in the present study the extractable Cu, Fe, Mg and Ni were determined using the method described by Gavlak et al (1994). Recent analysis of the samples from the same sites using the method described by Abedin et al (2012) resulted in much lower level of bioavailable elements specially for Cu (Narendrula et al, 2012;Nkongolo et al, 2013). Detailed information about reaction kinetics of the mobilisation and immobilisation process of heavy metals in soil and the importance of mass flow and diffusion for the availability of metals are still needed.…”
Section: Ajesmentioning
confidence: 99%
“…The mining, roasting and smelting of these elements have caused disastrous effects on the vegetation and overall environment (Amiro and Courtin, 1981;Gratton et al, 2000;Nkongolo et al, 2008;Vandeligt et al, 2011;Narendrula et al, 2012;. The effects have caused areas to become semi-barren to completely barren and studies on these outcomes have found sulfur dioxide Science Publications AJES emissions and metal particulates in soil to be the source.…”
Section: Introductionmentioning
confidence: 99%
“…Literature data report of numerous places in the world where Ni exceeds the permissible limit. For example, the Ni concentration of the soil was 1600-2150 mg kg −1 at Sudbury smelting area in Canada (Adamo et al 2002;Narendrula et al 2012), 303 mg kg −1 at Plovdiv non-ferrous metal smelter in Bulgaria (Bacon and Dinev 2005), 267 mg kg −1 around the Selebi Phikwe Cu-Ni mine in Botswana (Ngole and Ekosse 2012), 212 mg kg −1 at the former sludge disposal site in Denmark (Algreen et al 2014) and 122 mg kg −1 at the area of a former waste incineration plant in Czech Republic (Kacalkova et al 2014).…”
Section: Introductionmentioning
confidence: 99%